2017
DOI: 10.1016/j.ctarc.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between anti-depressant use and lung cancer survival

Abstract: Objectives In recent years, the anti-cancer properties of several commonly used drugs have been explored, with drugs such as aspirin and beta-blockers associated with improved cancer outcomes. Previous preclinical work demonstrated that tricyclic anti-depressants have antitumor efficacy in lung cancer. Our goal was to examine the association between anti-depressant use and survival in lung cancer. Materials and Methods We examined the association between use of common anti-depressants and survival in 1,097 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 51 publications
(61 reference statements)
1
37
0
1
Order By: Relevance
“…Of note, meta-analysis of tricyclic antidepressant users found a significant reduction in incidence of glioma and colorectal cancer 65 . Moreover, for lung cancer, tricyclic antidepressants or antihistamines significantly improved survival 40,66 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, meta-analysis of tricyclic antidepressant users found a significant reduction in incidence of glioma and colorectal cancer 65 . Moreover, for lung cancer, tricyclic antidepressants or antihistamines significantly improved survival 40,66 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, perturbing intracellular calcium homeostasis by stress hormones via the activation of adrenergic signaling has been implicated in the onset and progression of lung cancer [9,28], which may account for the cancerpromoting effect of psychological stress. Consistent with these, retrospective studies have demonstrated a clinical association between calcium channel blocker usage and reduced cancer mortality, particularly lung cancer [6,29,30]. Therefore, kavaʼs antistress properties may contribute to its anti-cancer potential.…”
Section: Discussionmentioning
confidence: 67%
“…Psychological stress was also found to be a significant predictor of lung cancer mortality [5]. Furthermore, epidemiological studies indicated extended lung cancer survival associated with antidepressant use [6]. These observations overall suggest the potential causality link between psychological stress and lung cancer risk/outcome, which has not been extensively explored in lung cancer management.…”
Section: Introductionmentioning
confidence: 99%
“…Another study of the associated risk of lung cancer with long term use of SSRIs and TCAs documented a protective effect for SSRIs and a slightly increased risk with TCAs. 24 Other antidepressants such as duloxetine, trazodone, and mirtazapine also showed a trend towards improved OS. 25 However, no specific trials or reviews have analyzed the potential antineoplastic effects of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…6 Non-small cell lung cancer (NSCLC) is the predominant lung cancer disease, but the effect of TCAs on NSCLC tumor cells is poorly studied. 7 SCLC is the more aggressive form with frequent early metastases, and the disease is usually asymptomatic until an advanced stage. 4 Although SCLC is a chemo-and radio-sensitive disease that usually responds to initial treatment, recurrence is very common, with only 6% of patients surviving 5 years from their initial diagnosis.…”
Section: Introductionmentioning
confidence: 99%